Postgraduate Education of Neurological Nurses — Preliminary Reports - Robert Ślusarz; Karolina Filipska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Postgraduate education for nurses is an integral part of professional development. Currently, in accordance with the legislation in force in Poland, a neurological nurse may improve their profession as part of self-education or as part of organized forms and types of postgraduate education by undergoing various specialized training, acquiring professional skills in the narrower fields of nursing or providing specific health services. Aim. The aim of the research was to analyse the postgraduate education of neurological nurses. Material and Methods. The research was conducted on a group of 128 nurses employed in 9 neurological centres in the Kuyavian-Pomeranian Voivodeship (Bydgoszcz, Toruń, Włocławek, Grudziądz, Świecie, Lipno). Postgraduate education was assessed by means of a diagnostic survey using a questionnaire survey technique. Results. It was shown that there are statistically significant differences between the age, experience and education of the respondents and the preferred form of education (p < 0.05) and awarding educational points for training (p < 0.05). It was also found that age and seniority in the neurology department differentiated the form of financing training (p < 0.05). Additionally, seniority is a factor that significantly differentiates the thematic specificity of the training (p < 0.05). Conclusions. The most popular form of postgraduate education is specialization and a specialist course. An important form of training is also participation in a conference/symposium. The vast majority of respondents stated that their trainings are financed by their own/private funds. It was found that the respondents lacked knowledge about training specific to neurological nurses, with the simultaneous need for such training. Among the difficulties/problems related to professional development, the most frequently indicated were the lack of time for training and difficulties with its financing. Almost half of the respondents expect to receive education/credit points for education. (JNNN 2020;9(2):71–75)